Effect of Individualized Whole-Body Vibration Exercise on Locomotion and Postural Control in a Person with Multiple Sclerosis: A 5-Year Case Report - Stefano La Greca; Stefano Marinelli; Rocco Totaro; Francesca Pistoia; Riccardo Di Giminiani (Applied Sciences)
The present study aims to investigate the multi-year effects (5 years) of individualized whole-body vibration (WBV) on locomotion, postural control, and handgrip strength in a 68-year-old man with relapse remitting multiple sclerosis (PwRRMS). The dose–response relationship induced by a single session was quantified by determining the surface electromyographic activity (sEMG) of the participant. The participant wore an orthosis to limit the lack of foot dorsiflexion in the weakest limb during walking in daily life. The gait alteration during walking was assessed at 1, 2 and 3 km/h (without the orthosis) through angle–angle diagrams by quantifying the area, perimeter and shape of the loops, and the sEMG of leg muscles was recorded in both limbs. The evaluation of postural control was conducted during upright standing by quantifying the displacement of the center of pressure (CoP). The handgrip strength was assessed by measuring the force–time profile synchronized with the sEMG activity of upper arm muscles. The participant improved his ability to walk at higher speeds (2–3 km/h) without the orthosis. There were greater improvements in the area and perimeter of angle–angle diagrams for the weakest limb (Δ = 36–51%). The sEMG activity of the shank muscles increased at all speeds, particularly in the tibialis anterior of weakest limbs (Δ = 10–68%). The CoP displacement during upright standing decreased (Δ = 40–60%), whereas the handgrip strength increased (Δ = 32% average). Over the 5-year period of intervention, the individualized WBV improved locomotion, postural control and handgrip strength without side effects. Future studies should consider the possibility of implementing an individualized WBV in PwRRMS.